A study on economic feasibility of fly ash and ground granulated blast furnace slag based geopolymer concrete. Issue 1 (March 2021) - Chithra, K S; Binoy, T; Harismitha, A; Ananth, R K; Deepa, M
Abstract: The rapid increase in the greenhouse gas emission has affected the ecological balance adversely which tends to the need of sustainable development in nature. The carbon dioxide produced during cement production is about 7% globally and it is the second most consumed product in the world. To mitigate this crisis, Geopolymer concrete (GPC) which constitutes industrial wastes like Ground Granulated Blast Furnace Slag (GGBS), flyash, rice husk is considered as a more eco-friendly and economically feasible alternative to Ordinary Portland Cement (OPC) based concrete. The reduction in the carbon dioxide emission from cement production can contribute significantly to the turning down of the global thermostat. The feasibility of production of GPC is much more safe, secure and reliable as it has more strength than conventional concrete [1]. The objective of the study is to compare the economic feasibility of conventional concrete and GPC. In this study, the rate analysis is done for optimum combination of flyash and GGBS based GPC and conventional concrete. From earlier studies flyash and GGBS based GPC is prepared by activating mixture of sodium silicate and NaOH solution. Optimum strength ratio obtained for flyash and GGBS is 1:1. In this study the analysis is done for GPC M 25 grade, conventional concrete of M 25 grade and is observed that GPC is more economical than conventional mix.